Study on high-speed stability of automobile based on aerodynamic lift feedback. (11th January 2022) - Zhang, Yong; Shi, Jiaqi; Xiao, Ye; Lin, Qibo; Mao, Fengzhao; Liu, Shuichang
For a long time, the impact of aerodynamic lift on the stability of high-speed vehicles has been studied only from the perspective of the aerodynamic force, and there is a lack of quantitative assessment of the vehicle body. In this paper, a model of multi-body dynamics of the vehicle was constructed by using an in-use vehicle model as the research object. Accuracy was verified using computational fluid dynamics (CFD) and compared with HD-2 (the second wind tunnel of Hunan University) wind tunnel test data. The stability of the vehicle under the condition of high-speed driving was analysed from two aspects of body acceleration and lateral displacement. The results show that the aerodynamic lift at high speed will reduce the maximum lateral acceleration and the maximum yaw acceleration of the vehicle body in the obstacle avoidance condition; and reduce the response speed of the vehicle body to driver's control. The anti-floating front bumper can effectively reduce aerodynamic lift and improve the high-speed driving stability of the vehicles.